2013
DOI: 10.3732/ajb.1300124
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in GERANYLGERANYL DIPHOSPHATE SYNTHASE 1 affect chloroplast development in Arabidopsis thaliana (Brassicaceae)

Abstract: Our results indicate that GGPS1 is a key gene in the chlorophyll biosynthetic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 69 publications
1
27
0
Order By: Relevance
“…SALK_140601 plants showed slow growth, had small pale-green leaves, and contained 70% carotenoids and chlorophylls compared with Col-0 plants (Supplemental Figure 6B and Supplemental Figure 7). We also observed the seedling-lethal phenotype of SALK_015098, which is consistent with a previous report (Ruppel et al, 2013). The developmental defects of GGPPS11 mutants suggested that GGPPS11 played an essential role in the generation of GGPP, which is the common precursor of several biologically important compounds (such as carotenoids, chlorophylls, and gibberellins), in Arabidopsis (Lange and Ghassemian, 2003).…”
Section: Dear Editorsupporting
confidence: 91%
“…SALK_140601 plants showed slow growth, had small pale-green leaves, and contained 70% carotenoids and chlorophylls compared with Col-0 plants (Supplemental Figure 6B and Supplemental Figure 7). We also observed the seedling-lethal phenotype of SALK_015098, which is consistent with a previous report (Ruppel et al, 2013). The developmental defects of GGPPS11 mutants suggested that GGPPS11 played an essential role in the generation of GGPP, which is the common precursor of several biologically important compounds (such as carotenoids, chlorophylls, and gibberellins), in Arabidopsis (Lange and Ghassemian, 2003).…”
Section: Dear Editorsupporting
confidence: 91%
“…2; Supplemental Fig. S1; Ruppel et al, 2013;Ruiz-Sola et al, 2016). This embryo lethal phenotype has never been observed in MEP pathway mutants (Phillips et al, 2008a).…”
Section: Different G11-defective Alleles Show a Range Of Phenotypes Fmentioning
confidence: 99%
“…2; Supplemental Fig. S1; Ruppel et al, 2013). By contrast, T-DNA insertions interrupting the C-terminal end of the G11 protein in alleles ggpps11-3 (SALK_085914, ggps1-3 or g11-3) and ggpps11-4 (SAIL_712_D06, g11-4) cause an arrest of embryo development ( Fig.…”
Section: Different G11-defective Alleles Show a Range Of Phenotypes Fmentioning
confidence: 99%
See 2 more Smart Citations